TEACHING READING COMPREHENSION USING A COMMUNICATIVE APPROACH TO CLASS VII STUDENTS AT MTS DARUSSALAMAH BARUH SAMPANG - Rohmah, Miftahur; Yuliarsih, Yuliarsih (The Ellite of Unira, 2026)
This research aims to find out how to overcome students' reading comprehension using a communicative approach to class VII students at MTs Darussalamah and to find out student responses in teaching reading comprehension using a communicative approach to class VII students at MTs Darussalamah. This research is a qualitative research. Data collection was obtained through classroom observations, interviews, documentation. The research results show that teachers use this communicative approach in students' reading comprehension with descriptive text material. Student responses in teaching reading comprehension to seventh grade students at MTS Darussalamah were that students showed high interest in learning English using a communicative approach. They feel enthusiastic and active in learning English. Students also feel attracted to the communicative approach, they find this media fun and easy to understand. Apart from that, the teacher succeeded in showing positive performance during learning by using a communicative approach.